Impact of Collaborative Care on Absenteeism for Depressed Employees Seen in Primary Care Practices: A Retrospective Cohort Study. Issue 1 (January 2018) - Adaji, Akuh; Newcomb, Richard D.; Wang, Zhen; Williams, Mark
Abstract : Objective: The impact of "real world" collaborative care on depression and absenteeism for depressed employees seen in primary care practices using objective employer absence data. Methods: A retrospective cohort study comparing depressed employees seen in primary care practices who enrolled for a "real world" collaborative care program to practice as usual (PAU) on objective absence days and depression response and remission at 6, and 12-month time periods. Results: Absence days were more in the collaborative care group compared with the PAU group at 3 and 6 months but at 12 months the difference was no longer statistically significant. Collaborative care led to better response and remission depression scores compared with PAU at 12 months. Conclusions: Collaborative care led to faster improvement in depression symptoms but did not translate to less time away from work.